Study of Development of Small-Competitive Cooperative and Business Developments in Dealing with Industrial Era 4.0 in West Java Province - Mukhtar Abdul Kader (STIE Malangkucecwara, 2022)
This study examines specifically about how the development of cooperatives and Micro Enterprises can compete in the industrial era 4.0, Of the 24,048 cooperatives and MSEs in West Java, 37.40% are classified as inactive, this indicates that cooperatives and micro-small businesses have not been able to compete with other business entities, especially the use of internet technology as the main characteristic of the industrial era 4.0, this inability causes high unemployment, which subsequently causing new poverty in society. In 2017 the poor in West Java totaled 4,168,440 or 8.71% and were in the 19th rank of 34 provinces in Indonesia. The purpose of this study is to find out how Cooperatives and Micro Small Businesses in West Java Province and How Strategies for Cooperative and Micro Business Development in West Java in facing the industrial era 4.0. The method used in this study is the field study method or literature study using secondary data and data analysis techniques used to use descriptive analysis and SWOT analysis (Strengths, Weakness, Opportunities, Threats). Cooperatives and civil society in West Java Province to survive need to adjust to the industrial era 4.0, namely to focus on improving managerial quality, products and services, using digital technology, increasing cooperation with banks, increasing business capital, building strong networks with the government, improving quality cooperation between cooperatives and small micro-business in ASEAN, improving service quality and the role of the community.